Percutaneous leverage reduction with kirschner-wire fixation assisted by elbow arthrography for pediatric radial neck fractures - Jiang, Hai; Li, Tao (Frontiers in Pediatrics, 2025)
ObjectiveRadial neck fractures in children can easily become complicated if not managed properly. Percutaneous reduction using the leverage technique with or without internal fixation with a Kirschner wire (K-wire) is a minimally invasive approach for treating angulated radial neck fractures in children. The study aims to evaluate the radiological and clinical outcomes of percutaneous leverage reduction assisted by elbow arthrography for pediatric radial neck fractures.MethodsFrom January 2016 to June 2020, we treated 47 children with angulated radial neck fractures, including 35 boys and 12 girls. The patient's age ranged from 2 to 13 years, with an average age of 6 years 9 months. According to Judet classification, 21 cases were classified as Type III, 15 cases as Type IVa and 11 cases as Type IVb. To overcome the difficulty of reduction caused by the absence of the ossified radial head centers in young children, we used intraoperative elbow arthrography to assist with the reduction. After achieving satisfactory reduction, one or two K-wires were inserted percutaneously to fix the fracture site and prevent reduction loss.ResultsAll cases were followed up for an average of 43 months, ranging from 24 months to 90 months. No radial head necrosis or synostosis of the proximal ulna and radius was observed during the long-term follow-up. No epiphyseal arrest or valgus of the elbow was noted at the end of the follow-up. According to the Metaizeau reduction classification, 42 cases were rated excellent, and 5 cases as good. Based on the Metaizeau clinical classification, 45 cases were excellent and 2 were good.ConclusionClosed reduction assisted by intraoperative elbow arthrography, combined with percutaneous leverage technique and internal fixation with K-wires, achieved satisfactory reduction and functional outcomes in children with angulated radial neck fractures, even in cases where the radial head ossification centers were not yet visible.